Analisis Tentang Penolakan Nasab Anak Dalam Perkawinan Yang Sah Dengan Sumpah Li’an Pada Putusan MA No.163K/AG/2011 - Rian Rizqi Putra Pratama; Musyaffa Amin Ash Shabah (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2019)
This study aims to analyze the result of Supreme Court ruling Number 163 K/AG/2011 AboutNasab’s Refusal Of a Legitimate Son By The Oat Of Li’an and how Islamic law and legislationgoverned it. And to explain what the status of the denied children’s passages is. This study usesinductive research methods and this type of research is a research library and the research approachemploys both qualitative and descriptive approaches. The results of the study show that the use ofother oaths to refuse the children's text in the Supreme Court Decision No. 163 K / AG / 2011 is inaccordance with the rules of Islamic law and statutory regulations, even though the wife is not willingto take the li'an oath, it still falls under the law. In accordance with the opinion of Imam Syafii that ifthe husband has completed his part, even though the wife does not do li'an. As well as changing thechild's nasab status which is denied by the father and only has a civil relationship with the mother andthe mother's family, while the father is free from the right to provide a living, this is in accordance withArticle 162 of the KHI.